Degradation of ionic liquids by a UV/H2O2 process and CMCase from novel ionic liquid-tolerant alkaliphilic Nocardiopsis sp. SSC4 - Atsushi Kurata; Shota Shimizu; Yutaro Shiraishi; Mihoko Abe; Nobutoshi Naito; Mihoko Shimada; Noriaki Kishimoto (Biotechnology & Biotechnological Equipment, 2017)
We demonstrated the degradation of two ionic liquids (1-butyl-3-methylimidazolium chloride, [BMIM]Cl, and 1-ethylpyridinium bromide, [EtPy]Br) that are useful for the solubilization of wood components. [BMIM]+ and [EtPy]+ were detected by thin-layer chromatography (TLC) and electrospray ionization–mass spectrometry (ESI-MS). [BMIM]+ was harder to degrade than [EtPy]+. Ultraviolet (UV) irradiation with 0.2% (v/v) H2O2 for 16 h degraded 1 mmol/L [BMIM]+, whereas UV irradiation alone degraded 1 mmol/L [EtPy]+. Additionally, we isolated an ionic liquid-tolerant alkaliphilic actinomycete, Nocardiopsis sp. SSC4. Strain SSC4 produced carboxymethylcellulase (CMCase) in the presence of 1.0% (v/v, 48.1 mmol/L) 1-ethyl-3-methylimidazolium trifluoromethanesulphonate ([EMIM]CF3SO3), which is useful for the extraction of cellulose-rich materials from wood. In the case of strain SSC4, CMCase was inducibly synthesized by more than 0.5% CMC. The addition of 0%–1.0% tryptone or 0%–2.0% yeast extract decreased the CMCase activity in a concentration-dependent manner. After cultivation of strain SSC4 with 1.0% (w/v) CMC medium (pH 9.0) for 48 h at 37 °C, the culture supernatant exhibited CMCase activity at 0.03 U/mg. The optimum reaction temperature of CMCase was 45 °C. CMCase was stable up to 37 °C for 20 h incubation. The degradation characteristics of [BMIM]+ and [EtPy]+ and the activity of CMCase in the presence of [EMIM]CF3SO3 may be useful for the development of a bioconversion system for biomass resources.